DESCRIPTION OF THE FOOD WASTE OF HOSPITALIZATION PATIENTS BASED ON PATIENT CHARACTERISTICS IN THE REGIONAL GENERAL HOSPITAL SANJIWANI GIANYAR - Ni Nyoman Suriyantini; Ni Made Yuni Gumala; Ida Ayu Eka Padmiari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
The food waste is the volume or percentage of food that is not consumed and discarded as garbage. Food waste are one of the simple indicators used to evaluate the success of hospital nutrition services. The purpose of this study is to describe of the food waste of hospitalization patients based on patient characteristics in the Regional General Hospital Sanjiwani Gianyar.The type of research used was observational with a cross-sectional study design, and samples were taken by purposive sampling which was 54 samples. The types of data collected are data on sample characteristics with interview methods using identity forms, food waste data with weighing methods, while hospital overview data, general description of nutrition installations, number of patients hospitalized, and number of nutritionists and waiters are obtained by recording through medical record books or notes related to data needed. Data analysis uses frequency distribution tables and cross tables which will then be described descriptively. The results of this study indicate that the high food waste in the age group 50-64 years 66,7%, male sex 52,4%, with elementary education 81,8%, employment as a private employee 53,8%, with a type of pregnancy complication disease 100%.Keywords: food waste, characteristics, hospital